Critical size defect regeneration by rhPTH collagen membrane as a new tissue engineering tool - Missana, Liliana Raquel (2014)
Recombinant Human Parathyroid Hormone (rhPTH 1-34) administration is an effective treatment to improve bone mass in osteoporosis. The aim of this study was to develop a Tissue Engeenering Tool for bone regeneration. We evaluated the efficacy of a freeze dried rhPTH membrane in calvarial critical size defect (CZD). 44 Wistar female rats (body weight 150 ± 50 g) with CZD (5mm) were divided into 4 groups: group 1: rhPTH membrane (rhPTHm); group 2: atelocollagen membrane (Cm); group 3: rhPTH and atelocollagen I (CrhPTHm); group 4: without any treatment (CG). All samples were evaluated on the 1st, 3rd and 6th weeks (wks) post-surgery by soft X-ray, histological and histometric studies. Soft X-ray results showed a radiolucent image with many irregular radiopaque areas. Histologically, rhPTHm was replaced by reticular bone (7%) since 3rd wk, and lamellar bone ossicles (30%) at 6th wk. Cm showed bone formation like composite bone type on wk 1st, 3rd and 6th (2%, 44% and 41% respectively). With CrhPTHm, bone formation was observed in all periods (2.4%, 48% and 53%), showing statistical difference with CG in the 3rd and 6th wks (p= 0.03 and 0.01). Our results demonstrated the effectiveness of a new biomaterial called CrhPTHm because its ability to regenerate calvarial CZD. Moreover, the membrane represents a new local intermittent delivery system allowing rhPTH slow release.